Talent strategy for retaining banking talent in Malaysia / Dewi Tajuddin - Tajuddin, Dewi (Universiti Teknologi MARA Sabah, Kota Kinabalu, 2016)
The main objective of this paper is to verify that using a talent strategy as a business strategy can retain banking talents in the Malaysian banking sector. This study has Talent Management Practices (TMP) as its direct variable to measure its relationship with Employee Value Proposition (EVP), which is the mediating variable. The two research objectives and questions of this study were answered by employing Structural Equation Modelling (SEM). The two results of this study reveal that there are significant positive relationships between Talent Management Practices and Employee Value Proposition for Malaysian banks. This study also found that Employee Value Proposition partially mediates the relationship of Talent Management Practices in the Malaysian banking sector. With these significant relationships, the findings of this study suggest it is timely for Malaysian local banks to use their own integrated talent strategy as a business strategy not only by developing but also retaining their talented bankers with attractive reward systems. In fact, due to the acute shortage of banking talent in Malaysia, there is a strong need to use talent strategy in managing the banking talent crisis. This is because talent management requires investment in intangible assets to manage the significant rise in the turnover rate in the Malaysian banking industry.